Headache As A Manifestation Of Paranasal Sinus Diseases: The Significance Of Plain Radiography (Texas Journal of Medical Science, 2026)
The prevalence of inflammatory diseases of the paranasal sinuses (PNS) remains consistently high, despite the introduction of modern diagnostic and treatment methods. This pathology occupies a significant place in the structure of outpatient visits to otorhinolaryngologists. In several regions, a particularly high incidence of sinusitis is observed; this is attributed to adverse environmental conditions, exposure to industrial factors, and the development of secondary immunodeficiency states within the population